Mental health for LGBTQI people: a policies' review. (19th May 2022) - Ventriglio, Antonio; Mirandola, Massimo; Galeazzi, Gian Maria; Amaddeo, Francesco; Pinna, Federica; Converti, Manlio; Fiorillo, Andrea; ,
Abstract: The mental health of lesbian, gay, bisexual, transgender, queer, intersexual (LGBTQI) individuals is significantly influenced by many factors such as difficulties in coming-out, poor acceptance, isolation and discrimination as well as minority-related stress. LGBTQI individuals, in fact, show a significant higher risk of mental health conditions, substance- use disorders and suicide. In addition, mental health services access may be difficult for personal and social barriers as well as a lack of adequate and specific mental health support. This review aims to assess and describe international policies, guidelines, position statements and recommendations regarding the promotion and protection of mental health rights for LGBTQI people. The search has been focussed on peer-reviewed papers, Governmental and Mental Health Association- Guidelines and Position Statements, Health Agencies - Guidelines and Position Statements (with a specific focus on mental health), LGBTQI Alliances and Foundations Publishing (with a specific focus on mental health). In addition, relevant international initiatives, and projects in the field of LGBTQI mental health will be described.